Composite measures of women's empowerment and their association with maternal mortality in low-income countries - Chiao-Wen Lan; Paula Tavrow (BMC, 2017)
Abstract Background Maternal mortality has declined significantly since 1990. While better access to emergency obstetrical care is partially responsible, women's empowerment might also be a contributing factor. Gender equality composite measures generally include various dimensions of women's advancement, including educational parity, formal employment, and political participation. In this paper, we compare several composite measures to assess which, if any, are associated with maternal mortality ratios (MMRs) in low-income countries, after controlling for other macro-level and direct determinants. Methods Using data from 44 low-income countries (half in Africa), we assessed the correlation of three composite measures - the Gender Gap Index, the Gender Equity Index (GEI), and the Social Institutions and Gender Index (SIGI) - with MMRs. We also examined two recognized contributors to reduce maternal mortality (skilled birth attendance (SBA) and total fertility rate (TFR)) as well as several economic and political variables (such as the Corruption Index) to see which tracked most closely with MMRs. We examined the countries altogether, and disaggregated by region. We then performed multivariate analysis to determine which measures were predictive. Results Two gender measures (GEI and SIGI) and GDP per capita were significantly correlated with MMRs for all countries. For African countries, the SIGI, TFR, and Corruption Index were significant, whereas the GEI, SBA, and TFR were significant in non-African countries. After controlling for all measures, SBA emerged as a predictor of log MMR for non-African countries (β = -0.04, P = 0.01). However, for African countries, only the Corruption Index was a predictor (β = -0.04, P = 0.04). No gender measure was significant. Conclusions In African countries, corruption is undermining the quality of maternal care, the availability of critical drugs and equipment, and pregnant women's motivation to deliver in a hospital setting. Improving gender equality and SBA rates is unlikely to reduce MMR in Africa unless corruption is addressed. In other regions, increasing SBA rates can be expected to lower MMRs.